Commonly Used Outcome Measurement Tools in Pediatric Physical Therapy Telerehabilitation in the Philippines: A Quantitative Cross-Sectional Descriptive Study - Arlene Chiong Maya; Therese Daniela Manaloto; Christian Rimando; Maria Eliza Dela Cruz; Daniel Stephen Banting; Alliana Cielo Equipaje; Noel Antonio Ipo; Jana Mae Mosi Ramos; Marc Jefferson Rillas; Jaycelle Anne Tajan (International Journal of Telerehabilitation)
With the COVID-19 pandemic, the adoption of telerehabilitation has rapidly increased to improve access and minimize cross-infection risk to patients. Nevertheless, Filipino pediatric physical therapists (PTs) must ensure that they conduct evidence-based procedures for specific tests and measures to determine patient outcomes. This investigation reported the most common pediatric outcome measurement tools (OMTs) used in telerehabilitation by Filipino pediatric PTs treating 0 to 21-year-olds in the Philippines. Validation and pilot testing of an adapted questionnaire on OMT usage was undertaken before dissemination via email and social media. Pediatric PTs reported that the commonly used OMTs in telerehabilitation are Gross Motor Function Measure (GMFM) (100%)—including both versions of GMFM-88 and GMFM-66 followed by Pediatric Balance Scale (PBS) (30%). These findings support the use of feasible OMTs in pediatric telerehabilitation due to their applicability in the online setting.